A quality picture: Perspectives on a distance learning programme - Andrea McIlroy (Flexible Learning Association of New Zealand, 2012)
Quality measures are now widely applied in higher education including in distance and open learning programmes. While quality assessment in distance education has traditionally focused on outputs and performance indicators such as retention and pass rates, there is now an increasing emphasis being placed on what quality means to the consumers of the product. Stakeholder models which take account of the needs and perspectives of different groups are also being applied. This paper reports part of a study conducted in the Business Studies faculty at Massey University which compares perceptions of quality in the extramural programme of three stakeholder groups - students, teaching staff and senior managers. A survey of students and staff highlighted areas of congruence and incongruence. Closing the gaps in perception should lead to improved assessments of quality.